AN EXPERIMENTAL COLLECTIVE INTELLIGENCE RESEARCH TOOL - Wang, Bei; Hoang, Dung; Daiz, Idris; Okpala, Chiedu; Sobh, Tarek M. (International Journal of Computing, 2014)
The Collective Intelligence Research Tool (CIRT) is an experimental software and hardware research tool. It provides an inexpensive and efficient alternative research implementation that demonstrates simulations of the collective behavior of self-organized systems, primarily social insects. The software focuses on 2D simulations of the woodchip-collecting behavior of termites and 3D simulations of the building behavior of wasps. The hardware simulation employs a Boe-Bot robot, which has the potential of simulating simple movements of a social insect, by extending its functionality through adding sensors and integrating a control chip.